2013
DOI: 10.1108/ijqss-12-2012-0026
|View full text |Cite
|
Sign up to set email alerts
|

Troublesome travellers – the service system as a trigger of customer misbehaviour

Abstract: Purpose -Customer misbehaviour, i.e. behaviour within the exchange setting that deliberately violates the generally accepted norms of conduct in such settings pose a problem for service organizations in several ways. Hitherto much research on customer misbehaviour has focused on psychological explanations and individual characteristics. This study broadens the perspective by taking structural factors of the service system into account. The purpose is to complement the existing literature on customer misbehavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In addition, and similar to what has been put forward in previous research on public transport (e.g. Enquist, Johnson, & Camén, 2005;Fellesson, Salomonson, & Åberg, 2013), the nature of the mobility service contains elements of a 'production logic' as it demands a level of large-scale efficiency and standardisation, with a tendency to develop pre-planned and comparatively inflexible operations. This inhibits demands for individualisation, flexibility and adaptability, demands which, for example, risk further enhancing consumers' feelings of being treated like 'commodities'.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, and similar to what has been put forward in previous research on public transport (e.g. Enquist, Johnson, & Camén, 2005;Fellesson, Salomonson, & Åberg, 2013), the nature of the mobility service contains elements of a 'production logic' as it demands a level of large-scale efficiency and standardisation, with a tendency to develop pre-planned and comparatively inflexible operations. This inhibits demands for individualisation, flexibility and adaptability, demands which, for example, risk further enhancing consumers' feelings of being treated like 'commodities'.…”
Section: Discussionmentioning
confidence: 58%
“…This implies that managers need to broaden their horizons and look beyond the individual situation and the individual customer's traits when seeking the causes of and remedies for misbehavior. As previous research findings indicate, systematic shortcomings in the service system design can trigger misbehavior (Fellesson et al, 2013). We feel that there should be good opportunities for working preventively by means of systematically analyzing and coordinating the operation's various subsystems, and by means of highlighting the frequently complex causal links that exist within a transport system.…”
Section: Implications For Managerial Practicementioning
confidence: 91%
“…In public transport, drivers as well as staff selling and checking tickets are subject to these forms of customer abuse (AFA Försäkring, 2009). Research has shown that customer misbehavior in public transport includes physical violence, verbal threats and abuse, drunkenness, the harassment of other passengers, unreasonable demands being placed on staff, and fare evasion (Boyd, 2002;Fellesson et al, 2013;Fullerton and Punj, 2004;Suquet, 2010). A recent study (see Table 1) of 88 transit agencies (U.S. and Canadian transit agencies and a Chinese BRT system) regarding which types of passenger assault have recently been problematic shows that verbal threats, intimidation, or harassment were considered to be the most problematic (TRB, 2011).…”
Section: Types Of Negative Customer Behaviorsmentioning
confidence: 99%
“…The literature indicates to executives that rules should be reworked in the light of episodes of customer abuse (FELLESON;ABERG, 2013). When a type of dysfunctional behavior becomes common, it is a sign that the service setting needs broader changes and it is appropriate for managers to rethink the reason behind their rules and their implementation (FISK et al, 2010), providing improvement of the services offered (ECHEVERRI, SALOMONSON, ABERG, 2012).…”
Section: Service Employees' Tactics and Dysfunctional Customer Behaviormentioning
confidence: 99%
“…When the consumer sovereignty myth makes room for the contradictions between what is propagated by the culture of consumer orientation and the limitations of the offer or service, disillusionment can lead to anger and dysfunctional customer behavior EVANS, 2013, KORCZYNSKI, OTT, 2004. Theory suggests that the promotion of customer orientation may be related to the behavior of customers in the environment (FELLESON;ABERG, 2013;LAM;KRAUS;AHEARNE, 2010).…”
Section: Final Considerationsmentioning
confidence: 99%